1992
DOI: 10.1128/aem.58.4.1394-1397.1992
|View full text |Cite
|
Sign up to set email alerts
|

Factors Stimulating Propagation of Legionellae in Cooling Tower Water

Abstract: Our survey of cooling tower water demonstrated that the highest density of legionellae, 104 CFU/100 ml, appeared in water containing protozoa, >102 MPN/100 ml, and heterotrophic bacteria, >10' CFU/100 ml, at water temperatures between 25 and 35°C. Viable counts of legionellae were detected even in the winter samples, and propagation, up to 10S CFU/100 ml, occurs in summer. The counts of legionellae correlated positively with increases in water temperature, pH, and protozoan counts, but not with heterotrophic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
34
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 24 publications
4
34
0
3
Order By: Relevance
“…Survey and monitoring of legionellae in environments are needed to prevent and control legionellosis. Legionella species are recovered from aquatic environments, such as rivers (18), lakes and ponds (8), cooling towers (13,21), and even tapwater (15). In water samples from these environments, cell numbers of legionellae were 102 to 105 cell/ml by direct counting with fluorescent antibody (FA) staining (8,18).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Survey and monitoring of legionellae in environments are needed to prevent and control legionellosis. Legionella species are recovered from aquatic environments, such as rivers (18), lakes and ponds (8), cooling towers (13,21), and even tapwater (15). In water samples from these environments, cell numbers of legionellae were 102 to 105 cell/ml by direct counting with fluorescent antibody (FA) staining (8,18).…”
mentioning
confidence: 99%
“…In water samples from these environments, cell numbers of legionellae were 102 to 105 cell/ml by direct counting with fluorescent antibody (FA) staining (8,18). On the other hand, colony numbers of legionellae from the water samples were usually lower than the number detected by direct counting (18,21). Several surveys also reported that legionellae were not isolated from many FA-positive samples, cooling tower water (13), tap-water (15), or river water (18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…) (Martinez-Manzanares et al) (Doyle et al; Leung et al; Martinez-Manzanares et al; O'Shea and Field; Stelzer and Jacob; Stelzer et al; Townsend) (Carmichael; Harding; Li, W. K. W. et a/.) (O'Shea and Field; Townsend) (Barrell; Gauthier et al; Martinez-Manzanares et al; Prabu and Mahadevan, Rice et al; Shadix and Rice, 1991; Townsend) (West et al) (Lye and Dufour, 1991; Martinez-Manzanares et al; Yamamoto et al)(Cargill et al;Paszko-Kolva et a/., 1991;Sanden et al;Yamamoto, H. et al) (Gennari and Dragotto; Leung et a/. ; O'Shea and Field) (Martinez-Manzanares et al; O'Shea and Field; Townsend) (Martinez-Manzanares et al; O'Shea and Field; Stelz and Zschock) (Martinez-Manzanares et al; O'Neill et al; Vanoy et al)…”
mentioning
confidence: 99%